2021
DOI: 10.1038/s41598-021-85782-6
|View full text |Cite
|
Sign up to set email alerts
|

Global sagittal alignment after surgery of right thoracic idiopathic scoliosis in adolescents and adults with and without thoracic hypokyphosis

Abstract: This study aimed to characterize global sagittal alignment in adolescent idiopathic scoliosis (AIS) with normal kyphosis (NTK, kyphosis > 10°) and with thoracic hypokyphosis (THK, kyphosis < 10°), before and after posterior spinal fusion, and compare them with asymptomatic controls. 27 AIS girls and young adults with right thoracic curves were included (seventeen with age ≤ 18 years, then age > 21). Biplanar radiographies were acquired at baseline, immediate post-operatively, 1-year and 2-year follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In a multivariate analysis of 371 subjects, Pasha et al [70,71] found that preoperative clusters, which shared significant differences in TK, predicted three clusters of 3D surgical outcomes with an accuracy of 64%. Regarding global alignment, Yeung et al [72] reported that hypokyphotic patients had adopted a more forwardleaning posture to compensate for global sagittal imbalance (indicated by SVA-SFD and sagittal OD-HA) compared to normokyphotic adolescent idiopathic scoliosis (AIS) subjects. However, this improved from immediate post-op to the 2-year postoperative follow-up.…”
Section: Sagittal Alignmentmentioning
confidence: 99%
“…In a multivariate analysis of 371 subjects, Pasha et al [70,71] found that preoperative clusters, which shared significant differences in TK, predicted three clusters of 3D surgical outcomes with an accuracy of 64%. Regarding global alignment, Yeung et al [72] reported that hypokyphotic patients had adopted a more forwardleaning posture to compensate for global sagittal imbalance (indicated by SVA-SFD and sagittal OD-HA) compared to normokyphotic adolescent idiopathic scoliosis (AIS) subjects. However, this improved from immediate post-op to the 2-year postoperative follow-up.…”
Section: Sagittal Alignmentmentioning
confidence: 99%
“…Making full use of the potential of EOS imaging system, Amabile et al proposed a new 3D parameter: the odontoid-hip axis (OD-HA) angle to quantify the 3D headpelvis alignment in young asymptomatic adults (12). Further studies showed that this parameter was quasi-invariant in a large part of the population, including older adults, both Caucasian and Chinese, and adolescent idiopathic scoliosis patients before and after surgery (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…For example, BPXR is used to follow up patients with idiopathic scoliosis treated with the in-brace method [ 9 ]. In patients with scoliosis, numerous X-ray images are taken to follow the patient’s growth or the impact of the treatment on the spine alignment [ 10 , 11 , 12 ]. With low irradiation, BPRX provides a useful tool for the radiological follow-up of patients with spinal deformities, especially children.…”
Section: Introductionmentioning
confidence: 99%